The Usage of Starfruit Extract (Averrhoa bilimbi) as a Supplement for Tilapia Seed - Yonarta, Danang; Anggana Rarassari, Madyasta; Ayuning Tyas, Dwi (Journal Of Artha Biological Engineering, 2025)
Tilapia (Oreochromis niloticus) has great potential in aquaculture due to its fast growth and delicious meat. However, challenges in providing quality feed and low nutrient intake hamper production. Administration of starfruit extract, rich in vitamin C and antibacterial compounds, can improve feed quality and support fish growth. Research shows that the addition of this extract can increase the weight, length, and survival of tilapia. Thus, using starfruit as a feed supplement at UPR Sumber Rezeki, Palembang, is expected to increase tilapia aquaculture productivity. Tilapia maintenance was carried out for 30 days, using 2 nets in a tarpaulin pond. The first net (P0) is for tilapia maintenance without the addition of starfruit extract, while the second net is for tilapia maintenance with the addition of starfruit extract (P1). Tilapia maintenance with periodic fasting for 30 days resulted in absolute length growth of 3.60 cm, absolute weight growth of 14.30 g, and 100% survival. The results of tilapia maintenance are classified as good compared to maintenance without the addition of starfruit extract.